Pengaruh ROA, Pertumbuhan Penjualan, Likuiditas dan Ukuran Perusahaan terhadap Struktur Modal Perusahaan Manufaktur Sektor Makanan dan Minuman di BEI - Metyria Imelda Hutabarat (Owner : Riset dan Jurnal Akuntansi, 2022)
Food and beverage companies are industries that compete in the world market and make major contribution to the value of national exports. Companies that have good capital structure have a good reputation and affect the high stock price. This research aimed to find out the effect of ROA, sales growth, liquidity, company size variable to capital structure variable in annual report listed on the Indonesia Stock Exchange year 2017–2019. The population are all food and beverage manufacturing companies listed on the Indonesia Stock Exchange, and obtained samples of amount 14 companies. The type of this research is a quantitative study. The data analysis used several analyzes, namely multiple linear analysis, the coefficient of determination test, the classical assumption test, R2 test, the F test, and the t test. Based on the results of this research, that partially profitability has significant positive effect on capital structure. Sales growth has no significant negative effect on capital structure. Liquidity has no significant negative effect on capital structure. Company size variable has significant positive effect on capital structure. The results of F test show that profitability, sales growth, liquidity, company size have significant positive effect on capital structure.